Preservação, sentidos e usos da memória e história. O patrimônio histórico-escolar em cena no Colégio de Aplicação da UFS (2000-2022) - Vieira, Paulo Mateus Silva (2023)
This study aims to investigate preservation and/or dissemination initiatives of institutional memory and/or school-historical heritage in laboratory schools, taking the Laboratory School of the Federal University of Sergipe (UFS) as the object of analysis. Considering that, the following specific objectives were defined: to identify efforts available in digital spaces that deal with institutional memory and its relationship with the preservation and/or dissemination of historical-school heritage in laboratory schools; to analyze the preservationist actions implemented in the Laboratory School of UFS; to characterize the initiatives of diffusion of the historical-school patrimony safeguarded in the Center of Research, Documentation and Memory (CEMDAP) of the Laboratory School of UFS; to analyze the contribution of preservation undertakings from CEMDAP to the History of Education. The time frame of this study refers to the first two decades of the 21st century, starting in the 2000s – period with greater production and dissemination of the aspects addressed in the study – and ending in 2022 – final year of data collection, carried out specifically through the observation of preservation and dissemination projects in laboratory schools published online. This investigation establishes dialogues with references concerned with the history of laboratory schools and with discussions on historical-educational heritage within the History of Education. The methodological procedures started with a survey of: a) all existing laboratory schools in Brazilian federal universities; and b) academic works related to the history and/or preservation of historical-school heritage in these institutions. The next step was to find, in digital spaces or collections, sources that gestured towards possible efforts to preserve and/or diffuse the institutional memory and the school-historical heritage in laboratory schools. The aim underlying this process was to construct a panorama of such activities undertaken in the aforementioned institutions. Moreover, the Laboratory School of UFS was taken as a specific case, so its initiatives were verified and discussed. The results point to actions for the preservation and dissemination of the institutional memory in laboratory schools, as well as to its exploration in research, teaching, and university outreach experiences. Although some efforts are linked to discussions on the notion of school-historical heritage, most of the results show the absence of this association. Finally, regarding the Laboratory School of UFS, the investigation revealed the development of projects via the Center for Research, Documentation and Memory concerned with the preservation and dissemination of the school-historical heritage and connected to pedagogical activities and to the increase in historiographical research.